A new deal between Science and Society through Citizen Science: the case study of sea-surface microplastics research - Bullo, Raffaella; Bianchelli, Silvia (Frontiers in Environmental Science, 2025)
In recent decades, environmental and public health crises have prompted discussions regarding the need to balance the right to work and the necessity of living in a healthy environment. A disconnect has arisen between scientific and civic societies due to communication breakdowns and a subsequent erosion of trust in the scientific community. Citizen Science serves to bridge this gap by fostering inclusion and promoting interaction as a democratic force for scientific processes. This article analyzes Citizen Science methodologies focused on monitoring sea-surface microplastics, assessing approaches to engage citizens in alignment with the principles established by the European Citizen Science Association. For this purpose, a literature review was conducted to identify eligible studies, utilizing three research databases with a specific focus on sampling methodologies. Furthermore, it examines sampling techniques and data management practices to ensure the integrity of data, in accordance with the European Union Marine Strategy Framework Directive. The findings indicate that Citizen Science initiatives aimed at monitoring sea-surface microplastics have emerged in academic literature in recent years but continue to be underutilized and/or under-published. The implementation of Citizen Science requires dedicated commitments and tools for straightforward adaptations or the development of new methodologies, with a focus on producing high-quality scientific data. Innovative approaches to Citizen Science can yield reliable data for research purposes and empower civil society to exchange knowledge with the scientific community, thereby promoting marine citizenship.